(3GdEYdGe HJGQjN Cgd GdESdGes - (3CHh HcQ Hf CMeO Hf eMeO Hf YeQ GdCSOj GdTgHj GdOeTbqj, Jbqj GdOjf , (B851 (3g`s; (3GdPgHj,J (B748 (3g` s
(3ChdgG (B:s
(3jHOC ef SfI (B781 s
(3BNQgG (B:s
(3jfJgi Edi SfI (B808 s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B51 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B13 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs